Analisis Peran Good Corporate Governance terhadap Kinerja Keuangan Perusahaan - Rahayu, Anggita Yuni; Christofel, Dicky Erfando (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this paper is to find out the influence of good corporate governance on a firm's financial performance. The type of research of this paper is using quantitative and literature review. The articles that were used in this paper were collected from several databases such as Scopus, Google Scholar, Science Direct, etc. The conclusion of this paper is that good corporate governance has a positive effect on a firm's financial performance.